(untitled) - Lâm, Thùy Trang (Can Tho, 2008)
The present research work attempts to contribute to understanding the practice of teaching listening skill. This study investigated belief of both teachers and students about the role of activating schemata in pre-listening activities in foreign language classes.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Study and teaching,Dạy và học,Research,Nghiên cứu